IMPLEMENTATION OF LITERACY MOVEMENT POLICY IN ELEMENTARY SCHOOL - Sumiati, Sumiati (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
The policy implementation stage is a very important stage in education policy including in the implementation of the School Literacy Movement policy. This type of research is a literature review, with stages, namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling a discussion, compiling conclusions based on the results of the analysis. The conclusion of this study is that the school literacy movement, especially in elementary school education units, has benefits both directly and indirectly. The essential aspects in the implementation process consist of communication factors, resources, bureaucratic attitudes, and procedure standards. The role of the principal in implementing literacy policies in schools is through effective principal-teacher interaction leading to effective literacy learning exploration results, namely by communicating with teachers, especially in reflection and improving professional skills, for example coaching.